2006
DOI: 10.1074/jbc.m505266200
|View full text |Cite
|
Sign up to set email alerts
|

A Peroxisome Proliferator-activated Receptor-γ Agonist, Troglitazone, Facilitates Caspase-8 and -9 Activities by Increasing the Enzymatic Activity of Protein-tyrosine Phosphatase-1B on Human Glioma Cells

Abstract: Despite dramatic advances in adjuvant therapies, patients with malignant glioma face a bleak prognosis. Because many adjuvant therapies seek to induce glioma apoptosis, strategies that lower thresholds for the induction of apoptosis may improve patient outcomes. Therefore, elucidation of the biological mechanisms that underlie resistance to current therapies is needed to develop new therapeutic strategies. Here we proposed a novel mechanism of proapoptotic effect induced by a pharmacological peroxisome prolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 44 publications
(34 reference statements)
2
45
0
Order By: Relevance
“…The ability of PPARγ agonists to enhance apoptosis induced by TRAIL has been shown in several other types of cancer cell lines [37,[40][41][42][43]. Lu et al [40] reported that PPARγ agonists of the thiazolidinedione class sensitize breast cancer cells to TRAIL by reduction of cyclin D3 through decreasing cyclin D3 mRNA levels and inducing cyclin D3 proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of PPARγ agonists to enhance apoptosis induced by TRAIL has been shown in several other types of cancer cell lines [37,[40][41][42][43]. Lu et al [40] reported that PPARγ agonists of the thiazolidinedione class sensitize breast cancer cells to TRAIL by reduction of cyclin D3 through decreasing cyclin D3 mRNA levels and inducing cyclin D3 proteasomal degradation.…”
Section: Discussionmentioning
confidence: 99%
“…Troglitazone (TG) is an activator of protein tyrosine phosphatase 1B (PTP1B); it reduces PY705-STAT3 and promotes apoptosis in human primary gliomas (34). We tested whether TG stimulated p53 expression and apoptosis in CLL.…”
Section: The Phosphatase Activator Troglitazone Induces P53 Expressiomentioning
confidence: 99%
“…The PTEN inhibitor dipotassium bisperoxo(pyridine-2-carboxyl)oxovanadate (bpV(pic)) (28) and the Src homology 2-containing protein tyrosine phosphatase-1 (SHP-1) inhibitor ␣-bromo-4-(carboxymethoxy)-acetophenone (SHPI; Ref. 29) were purchased from Calbiochem. Lipofectin reagent was obtained from Molecular Probes.…”
Section: Animals and Reagentsmentioning
confidence: 99%